(untitled) (AYUSHDHARA, 2025)
Alcoholic liver disease (ALD) encompasses a spectrum of liver conditions caused by chronic alcohol use, beginning with fatty liver, advancing to alcoholic hepatitis, and culminating in alcoholic cirrhosis- the irreversible and most severe stage of alcohol-induced liver damage. Diagnostic criteria for ALD are based on liver function tests and ultrasound (USG) of the abdomen to assess changes in liver function and structure. Yakritddalyudara and the signs and symptoms of ALD go parallel to each other. A 50-year-old male with a 22-year history of chronic alcohol consumption presents with yellowing of the sclera and urine, loss of appetite, abdominal distension, and bilateral lower limb and abdominal pain persisting for the past week. With the increased level of LFT and USG-abdomen report suggesting hepatomegaly with fatty changes, was examined and diagnosed as alcoholic liver disease and treated with Shamana and Shodana Chikitsa. The patient showed good improvement with normalization of appetite, bilateral lower back pain, abdominal pain, and yellowish discoloration of the sclera and urine. Lab investigations revealed a significant reduction in relief of symptoms, 83.5% improvement in total bilirubin, 48% improvement in AST, 29% improvement in ALT, and 8.4% improvement in ALP. In Shodana karma, Nitya virechana is adopted, and as a Shamana modality, Nidana Parivarjana, Dosha Pratyanika, and Vyadhi Pratyanika Chikitsa were adopted and showed a significant result in reducing signs and symptoms. It shows the effectiveness of the treatment method adopted.